2020
DOI: 10.1186/s40658-020-00311-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sampling schedules on [177Lu]Lu-PSMA dosimetry

Abstract: Background: Individualized dosimetry is recommended for [ 177 Lu]Lu-PSMA radioligand therapy (RLT) which is resource-intensive and protocols are often not optimized. Therefore, a simulation study was performed focusing on the determination of efficient optimal sampling schedules (OSS) for renal and tumour dosimetry by investigating different numbers of time points (TPs). Methods: Sampling schedules with 1-4 TPs were investigated. Time-activity curves of the kidneys and two tumour lesions were generated based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 34 publications
(81 reference statements)
2
18
0
1
Order By: Relevance
“…Limited data are available regarding simplified dosimetry of [ 177 Lu]Lu-PSMA RLT. Rinscheid et al [34] demonstrated that a single SPECT/CT measurement at 52 h p.i. yielded good approximations for the time-integrated activity coefficients of the kidney, consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited data are available regarding simplified dosimetry of [ 177 Lu]Lu-PSMA RLT. Rinscheid et al [34] demonstrated that a single SPECT/CT measurement at 52 h p.i. yielded good approximations for the time-integrated activity coefficients of the kidney, consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting approach for single-time-point-based renal dosimetry, originally introduced by Hänscheid et al for DOTATATE-therapies uses an approximate method to estimate the area under the timeactivity curve [33]. The principle validity of this approach also for PSMA-targeted therapies was shown by Rinscheid et al [34]. All of these studies showed that dosimetric calculations for the kidneys but also tumor lesions seem possible based on data from a single imaging time-point.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we chose 4h as the second time point for patient convenience as it enables imaging before discharge on the day of therapy. (13). In our analysis, the single time point mixed model often performed better than the two time point mixed model, suggesting that addition of the early measurement may not be necessary.…”
Section: 5mentioning
confidence: 64%
“…Exponential functions are customarily used to fit the measured time-activity data, and two or three sampling points per exponential term and measurement period up to three to five times the effective half-life are recommended (3). A number of recent studies have considered simplified personalized renal dosimetry in PRRT (4)(5)(6)(7)(8)(9)(10)(11)(12) and Lu177-PSMA therapy (13,14). In particular, methods for approximating the PRRT TIA using a single activity measurement, introduced for Lu-177 DOTATATE by Hanscheid et al (4) and for Y-90 DOTATOC by Madsen et al (5), have gained popularity.…”
mentioning
confidence: 99%
“…Für die Dosimetrie in der Radionuklidtherapie ist folglich der zu erwartende Fehler für die Tumordosimetrie deutlich größer als der Fehler bei der Bestimmung der Strahlendosis auf vergleichsweise große Risikoorgane wie Leber, Nieren und Milz. Aus Sicht der Pharmakokinetik ist die Genauigkeit der Tumordosimetrie zudem stark durch den letzten verfügbaren Bildgebungszeitpunkt beeinflusst[43,54,55].Von ihrem Grundgedanken her hat die Dosimetrie im Rahmen von interner oder externer Strahlentherapie zum Ziel, die Strahlendosis des gesunden Gewebes zu minimieren, bei gleichzeitiger Maximierung der Tumordosis, um das therapeutische Fenster maximal auszuschöpfen. Für die externe Strahlentherapie ist dieser Ansatz vollständig innerhalb der klinischen Routine etabliert und umsetzbar, da im Rahmen der externen Strahlentherapie die Zieldosis auf das maligne Gewebe während der Therapiesitzung kontrolliert unter Berücksichtigung umliegender Risikoorgane eingestrahlt werden kann.…”
unclassified